Measurement Of Thermal Comfort At Classroom: A Case Study In UTeM - Yong Thau Foong, Stanley (2008)
Thermal comfort is a condition of mind which expresses satisfaction with the surrounding thermal environment. A person’s perception of thermal comfort is affected by air temperature, mean radiant temperature, air velocity, relative humidity, metabolic rate for work activities and clothing insulation. Thermal comfort in classrooms has to be considered seriously because of the negative influence on learning and the potential for energy conservation through careful temperature control. In recognition the importance of thermal comfort in classroom, the objectives of study are to determine the response of occupants regarding to thermal comfort at classroom in UTeM, measure the actual thermal comfort at classroom in UTeM, and propose the solutions in order to improve or maintain the thermal comfort at classroom in UTeM. Determination of occupants’ responses was obtained through observation method associated with a questionnaire. Measurement of actual thermal comfort in classroom is performed via direct technical measurement associated with a thermal comfort monitor to determine the PMV and PPD. Meanwhile, the thermal comfort improvement was proposed based on engineering controls and administrative controls. The results of occupants’ responses show that BK 12 in morning and afternoon sessions and BK 5 at evening session are the most dissatisfied classrooms. However, the results of direct technical measurement show also that the BK 12 in morning and afternoon sessions and BK 5 at evening session are the most dissatisfied classrooms. When compared between each other, the direct technical measurement has confirmed the findings of occupants’ responses at morning session, but it is not at afternoon and evening sessions as they show the negative correlations.